Pengaruh remunerasi, motivasi kerja dan kepuasan kerja terhadap kinerja fakultas ekonomi dan bisnis pada UPN “Veteran” Jawa Timur - Nurhidayah, Siti; Munari, Munari (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to examine and prove the effect of remuneration, work motivation, and job satisfaction on the performance of the Faculty of Economics and Business, of University Pembangunan Nasional